Language changes associated with Fast ForWord-Language: evidence from case studies. - Loeb DF; Stoke C; Fey ME (American Journal of Speech-Language Pathology, 2001)
Based principally on reports of two experimental investigations, the Scientific Learning Corporation claims that Fast ForWord-Language (FFW-L) yields 1-1/2 to 3 years language gain over a 6-week period. We evaluated various aspects of this claim by measuring the language changes of four children who received FFW-L language intervention in their homes. Language change was assessed immediately following intervention and 3 months later, using standardized language measures, spontaneous measures of syntactic complexity, reading measures, pragmatic measures, and parent and teacher reports. Three of the four children successfully completed FFW-L, and all made gains on some of the same standardized measures used by P. Tallal et al. (1996), although the improvements we observed were generally smaller than those previously reported. All children also made gains on measures of pragmatic performance. However, very few changes were observed in the children's Developmental Sentence Scores (DSSs), indicating that gains in productive use of grammar changed only marginally. One child showed evidence of gains in standard assessment of his phonological awareness skills. According to questionnaire data, parents and teachers did not report many differences in performance after intervention; however, parental satisfaction with the program was generally high. Sixty-one percent of the gains observed at posttesting were maintained 3 months following intervention; however, a number also were not maintained. Of the total 595 items assessed at pretest and posttest, significant positive change occurred on 58 or 10% of the items. Our findings suggest that, although FFW-L delivered at home by parents may lead to some important changes in children's performance on structured tasks, broad, dramatic gains in spontaneous language use are less likely and may not be long-lasting. Future experimental investigations should include measures of pragmatic performance to substantiate the preliminary findings of these case studies.